Carbon deposition from biotar by fast pyrolysis of palm empty fruit bunch - Rozhan, Alya Naili; Hamzah, Mohd. Salleh; Purwanto, Hadi (Elsevier, 2016)
This paper presents a technology to recover carbon available in tar vapor produced from fast pyrolysis of oil palm empty fruit bunch, EFB using porous biochar pellets by employing chemical vapor infiltration, CVI method. By combining slow and fast pyrolysis of EFB, a process was developed employing CVI method, to produce a value-added EFB product. In this developed process, porous biochar produced from slow pyrolysis of EFB pellet was introduced as a medium for tar decomposition to take place. Tar vapor infiltrated within biochar pores and then decomposed into carbon and gases where carbon was deposited on the pore surface. Non-condensable gases can be collected and biotar can be recovered in the form of carbon deposit before being utilized as a renewable energy source by itself. The purpose of this work is to investigate the possibility of using EFB-derived biochar as a medium for tar decomposition and carbon deposition during secondary pyrolysis reaction. Temperature 450°C was found to be the optimum temperature for this secondary pyrolysis reaction to take place within the EFB-derived biochar leaving solid carbon within the available pores. The product of this tar filtering process was carbon-deposited biochar – a potential candidate to be used as an alternative fuel source.